How do you evaluate e^( ( 13 pi)/8 i) - e^( ( pi)/4 i) using trigonometric functions?

1 Answer
Feb 16, 2016

e^((13pi)/8i) - e^(pi/4i) = (sqrt(2-sqrt(2))-sqrt(2))/2-i*(sqrt(2+sqrt(2))+sqrt(2))/2 ~=
~= -0.3244-1.6310*i

Explanation:

First of all, let's recall the Euler's formula that imaginary exponents:
e^(i*x) = cos(x)+i*sin(x)

Let's evaluate two terms of the original expression separately and then determine the difference between them.

Based on this formula,
e^((13pi)/8i) = cos((13pi)/8) + i*sin((13pi)/8)

Simple property of trigonometric functions that immediately follows from their definition are:
cos(x+pi) = -cos(x)
sin(x+pi) = -sin(x)
cos(x+pi/2) = -sin(x)
sin(x+pi/2) = cos(x)

Since (13pi)/8= pi+(5pi)/8 and (5pi)/8=pi/2+pi/8, the expression above can be further evaluated to
-cos((5pi)/8)-i*sin((5pi)/8) = sin(pi/8)-i*cos(pi/8)

To determine sin(pi/8) and cos(pi/8), recall the formula for cos of double angle:
cos(2x)=2cos^2(x)-1
From it for x=pi/8 follows:
cos^2(pi/8) = 1/2(1+cos(pi/4)) = 1/4(2+sqrt(2))

cos(pi/8)=1/2sqrt(2+sqrt(2))

From sin^2(x)+cos^2(x)=1 for x=pi/8 follows
sin^2(pi/8) = 1-1/4(2+sqrt(2)) = 1/4(2-sqrt(2))

sin(pi/8)=1/2sqrt(2-sqrt(2))

So, the first term in the original expression is
e^((13pi)/8i) = 1/2sqrt(2-sqrt(2))-i*1/2sqrt(2+sqrt(2))

The second term in the original expression is
e^(pi/4i) = cos(pi/4) + i*sin(pi/4) = sqrt(2)/2+i*sqrt(2)/2

The difference between the first and the second terms is:
(sqrt(2-sqrt(2))-sqrt(2))/2-i*(sqrt(2+sqrt(2))+sqrt(2))/2